STRATEGI BISNIS UNTUK MENINGKATKAN MINAT ENTERPRENEUSHIP MAHASISWA FMIPA UNIVERSITAS NEGERI MALANG - Kridha Pusawidjayanti; Vita Kusumasari; Asmianto Asmianto; Latifah Mustofa Lestyanto (Fakultas Sains dan Teknologi, 2023)
Partners in this community service activity are FMIPA Universitas Negeri Malang students who need insight into entrepreneurship. The problem with this service partner is that the financial source is only from the parents, while the parents' economic conditions (student guardians) are in the lower middle class, while the needs of students are also increasing. So that students can continue to continue their studies and be able to innovate and develop their potential, additional funds are needed. One way is to start entrepreneurship. Based on the partner's problems, the Dedication Team of the Mathematics Department of FMIPA Universitas Negeri Malang provided a solution, namely by providing training regarding the entrepreneurial mindset for FMIPA students with several kinds of material such as: why students should be entrepreneurs, finding personal branding and digital marketing. Keywords: Business, Student, Entrepreneur